1998
DOI: 10.1037/0022-3514.74.5.1133
|View full text |Cite
|
Sign up to set email alerts
|

Depressives' future-event schemas and the social inference process.

Abstract: Two studies examined depressed and nondepressed perceivers' characterizations and thoughtful inferences about the behaviors of another person. In Study 1, depressed and nondepressed participants under a cognitive load or no load were asked to make either dispositional (ability) or situational (task ease) inferences about a target's videotaped performance. When cognitive resources were limited, depressed compared with nondepressed individuals made more pessimistic characterizations. No depression-related differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
36
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 53 publications
(89 reference statements)
6
36
1
Order By: Relevance
“…To that end, the present study focuses on the processing of information concerning future self-referent events and experiences, which has also been shown repeatedly to be negatively biased in NSD (Butler & Mathews, 1983 ;Andersen et al 1992 ;Reich & Weary, 1998).…”
Section: Cognitive Processes In Sd and Nsdmentioning
confidence: 99%
“…To that end, the present study focuses on the processing of information concerning future self-referent events and experiences, which has also been shown repeatedly to be negatively biased in NSD (Butler & Mathews, 1983 ;Andersen et al 1992 ;Reich & Weary, 1998).…”
Section: Cognitive Processes In Sd and Nsdmentioning
confidence: 99%
“…More specifically, previous research by Andersen and her colleagues (Andersen, 1990;Andersen, Spielman, & Bargh, 1992) has shown that the pessimistic future-event expectancies held by depressed students are chronically accessible and efficient and that they are applied to predictions about both the self and others; in contrast, the more positive expectancies of nondepressed students, although neither chronic nor efficient, are associated with more optimistic predictions about the self and others. Reich and Weary (1998) recently examined in two studies whether these stored knowledge structures could impact the dispositional inference process. In their research, Reich and Weary asked depressed and nondepressed participants to observe a target's relatively successful performance on a test of cognitive ability and then to make inferences about his or her general level of ability.…”
Section: Dispositional Inference Processmentioning
confidence: 99%
“…As a result, it is susceptible to disruption by factors that reduce the motivation or the ability to process information effortfully. Several studies, for example, have demonstrated that participants who are unmotivated or cognitively distracted (i.e., diverting attention to another task) fail to use situational information to correct their initial dispositional judgments (e.g., Gilbert et al, 1988;Reeder, 1997;Reich & Weary, 1998;Trope & Alfieri, 1997;Yost & Weary, 1996).…”
Section: Stage Models Of the Social Inference Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost without exception, attribution theorists and researchers have focused on the assimilative effects of contextual information on behavior categorization and characterization processes (Gilbert et al, 1988;Krull & Erickson, 1995;Reich & Weary, 1998;Trope, 1986;Trope & Alfieri, 1997;cf. Weary & Reich, in press).…”
mentioning
confidence: 99%